Partisipasi Masyarakat Dalam Perencanaan dan Pemanfaatan Alokasi Dana Desa di Desa Tanjung Jorong Kecamatan Tualan Hulu Kabupaten Kotawaringin Timur: Community Participation in Planning and Utilization of Village Fund Allocation in Tanjung Jorong Village, Tualan Hulu District, East Kotawaringin Regency - Megawati, Indah; Febry, Hermanus (Pencerah Publik, 2017)
The purpose of this study was to find out how community participation in planning and utilization of village fund allocations in Tanjung Jorong Village, Tualan Hulu District, East Kotawaringin Regency. The method used in this study is a descriptive qualitative approach, which is the source of data in this study, namely the Chief of Bangkuang Village, Village Staff and several people in Tanjung Jorong Village, Tualan Hulu Sub-District, East Kotawaringin Regency. Data collection techniques carried out by observation, interviews, and documentation. The results of this study indicate that the level of participation of the Tanjung Jorong Village community can be seen in the stages of planning, utilization, and supervision classified as low. As expressed by Pusic (2006) that planning without taking into account community participation will make planning only on paper. And supporting and inhibiting factors are a) Cooperative and communicative support from the district government and village government in regulating ADD in Tanjung Jorong Village area so that accountability reporting can be reported with a predetermined time b) Village government attitudes that are transparent, accountable in utilizing ADD and c) Limitations on ADD funds that are still minimalist.